Effects of works councils on firm-provided further training in Germany - Stegmaier, Jens [Verfasser] (My University, 2012)
"Unions are an important indicator of various measures of firm performance in Anglo-Saxon countries. The same is true for the German analogue of the workplace union, the works council. Using German establishment data, I examine the impact of works councils on further training. I employ pooled logit and count-data models to analyse the further training activity and intensity of German firms. Because the treatment variable may suffer from endogeneity, I also adopt linear and nonlinear instrumental variable techniques. The analysis reveals a positive impact of works councils on firm-provided training and provides slightly weaker evidence for firm-size differentials in workplace representation. I conclude that enhanced management - employee relations foster the training efforts of firms." (Authors' abstract, BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; S 3.5.4 Sozialpartner; Betriebliche Weiterbildung; Personalentwicklung; Weiterbildungsverhalten; Einflussfaktor; Betriebsrat; Betriebsgröße; IAB-Betriebspanel